PENAMPILAN PERTUMBUHAN AYAM PERSILANGAN KAMPUNG DAN BANGKOK - Rahayu, B. W. I.; Widodo, A. E. P.; Sarunggalo, R. (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2010)
This study was carried out for four months by using 48 chicks which consist of the progeny of interse Bangkok Chicken, interse Kampung Chicken, Crossing of Bangkok-Kampung and Crossing of Kampung Bangkok. Variables of the study were average body weight, feed Consumption and feed Efisiency. A Complete randomized design was used in this study. The result showed the highest average body weight and feed consumption in progeny interse Bangkok Chicken, however the best feed efisiency found in crossing of Kampung-Bangkok.